PENGARUH MEDIA PEMBELAJARAN AUDIO VISUAL DALAM MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MI MIFTAHUL HUDA BABAKAN TENGAH - Abdul Muis, Cecep; Nina Nur Sholehah (Program Studi Pendidikan Agama Islam, 2024)
The influence of audio-visual learning media is that teachers use audio-visual media in the process of increasing students’ understanding of the subject of Islamic cultural history at MI Miftahul Huda Babakan Tengah. This research is quantitative research with the object of study being audio-visual learning media. The method used in this research is an experimental method with a Nonequivalent Control Group Design. The population used was all fourth grade students at MI Miftahul Huda, and the sample taken in this research was the entire population, namely 29 students. The tests used were pretest and posttest, and the data were analyzed using SPSS. The data analysis technique for this research uses the t-test. The results of this research show an increase in the pretest and posttest, this is proven by obtaining a significance value of 0,000. In accordance with the decision rule of 0,000 < 0,05. Ha is accepted and Ho is rejected. This means that audio-visual learning media has an influence in increasing students’ understanding of the class IV Islamic cultural history subject at MI Miftahul Huda. Then, the average posttest score for the experimental class was 82,66 while the control class was 45,00. From these results, it can be seen that there are differences, thus it can be concluded that audio-visual learning media has an influence in increasing students understanding of the class IV Islamic cultural history subject at MI Miftahul Huda.